Correlation Between Amniotic Fluid Index and Estimated Fetal Weight in Third Trimester of Pregnancy - Parveen, Rafia; Ahmed, Akhteruddin; Mohiuddin, AS; Rahman, Shaikh Shofiur; Paul, Tapesh Kumar (Bangladesh Medical Journal, 2014)
This study was conducted to find out the correlation between amniotic fluid index (AFI) & estimated fetal weight (EFW) in third trimester of pregnancy. This cross sectional study was carried out on 105 women with normal singleton pregnancies at third trimester. The pregnant women were subdivided into three groups. The AFI & EFW were evaluated according to gestational age groups & fetal sex. Significant positive correlations were found between estimated fetal weight and amniotic fluid index in female fetuses of all three groups. In male fetuses, there was a significant positive correlation between AFI & EFW in group III (38 to 40 weeks), but insignificant correlation in other two groups. No study was conducted previously in Bangladesh to see the relationship between AFI & EFW. This study shows that amniotic fluid volume can be evaluated more precisely during third trimester of pregnancy by taking estimated fetal weight into consideration in third trimester of pregnancy. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18669 Bangladesh Medical Journal 2011 Vol.40(3):21-23